2008
DOI: 10.1007/s00330-008-1063-1
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic field-based navigation for percutaneous punctures on C-arm CT: experimental evaluation and clinical application

Abstract: The aim of this study was to prospectively evaluate the needle visualization and placement error and use of an electromagnetic field-based tracking navigation device for puncture procedures based on C-arm CT (CACT) images. A commercially available navigation device was mounted on an angiographic X-ray system setup for CACT. After the target was defined, needle placement was performed under real-time visualization of the virtual needle in CACT images. The final, real needle position was assessed by CACT. Punctu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
0
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 23 publications
2
29
0
5
Order By: Relevance
“…The authors concluded that CT/EMT guidance led to high accuracy with regard to needle placement, thus reducing time and potentially radiation exposure in comparison with conventional CT alone. CACT/EMT guidance is a relatively new innovative technique [20,23]. Compared with data obtained with exclusive CT or CACT guidance in the literature [7, 12, 14, 24 -26], our results showed comparable diagnostic yield values for CACT/ EMT-guided biopsy procedures.…”
supporting
confidence: 68%
See 4 more Smart Citations
“…The authors concluded that CT/EMT guidance led to high accuracy with regard to needle placement, thus reducing time and potentially radiation exposure in comparison with conventional CT alone. CACT/EMT guidance is a relatively new innovative technique [20,23]. Compared with data obtained with exclusive CT or CACT guidance in the literature [7, 12, 14, 24 -26], our results showed comparable diagnostic yield values for CACT/ EMT-guided biopsy procedures.…”
supporting
confidence: 68%
“…However, C-arm cone-beam CT images provide restricted image quality in terms of contrast resolution [15 -19]. An approach to improve the accuracy of tumor targeting despite lower image quality may be the coupling of C-arm cone-beam CT with an electromagnetic navigation system in the guidance of biopsies [20]. To date, only a few studies addressing the role of C-arm conebeam CT-based electromagnetic tracking (EMT) of percutaneous biopsies have been published, and this guiding technique seems to be relatively new to the field of interventional radiology [17,20].…”
mentioning
confidence: 99%
See 3 more Smart Citations